The effects of taxes and charges on saving incentives in the UK - Stuart Adam; Jonathan Shaw (Institute for Fiscal Studies (IFS), 2016)
Individuals in the UK can save in many forms, such as bank accounts, pensions, housing, shares and Individual Savings Accounts (ISAs). The tax treatment of these different vehicles and underlying assets varies widely and this can affect the attractiveness of saving in different forms for people in different circumstances. Recent years have seen several major reforms to the tax treatment of different forms of saving, and further changes are currently under consideration. It is therefore crucial to understand what the current tax regime and (actual and hypothetical) reforms imply for incentives to save in different forms. In this report (i) we describe the forms in which household wealth is held, (ii) we set out the effects of the current UK tax system on the incentive to save in different assets, (iii) we consider the implications of a number of reforms due to be introduced or currently under consideration, and (iv) we analyse the effect of two non-tax features - employer matching of pension contributions and fund charges - on the attractiveness of investing in different assets ...
Keywords: 330; tax; saving